Experimental investigation of air distribution in an airliner cabin mockup with displacement ventilation. (15th March 2021) - Liu, Mingxin; Chang, Di; Liu, Junjie; Ji, Shengcheng; Lin, Chao-Hsin; Wei, Daniel; Long, Zhengwei; Zhang, Tengfei; Shen, Xiong; Cao, Qing; Li, Xingyang; Zeng, Xiaojing; et al.
Abstract: The commercial airliner cabin environment is very important for passengers and crew, and airflow and contaminant concentration distributions in cabins play a key role in creating a comfortable and healthy cabin environment. To study the airflow and the contaminant concentration distributions in airliner cabins, this investigation used a seven-row aircraft cabin mockup with well-controlled thermo-fluid boundary conditions. This study measured air temperature and velocity distributions with displacement ventilation by using T-type thermocouples and ultrasonic anemometers (UA), and contaminant distributions by using tracer gas and particle from a generator to simulate contaminant breathed out by a passenger. This paper discusses our effort to control the thermo-fluid boundary conditions with high accuracy. The measured results show that the air temperature was stratified and the air velocity was low. The contaminant was not transported to the other side of the cabin by the displacement ventilation system and was removed effectively through the ceiling exhaust. The Richardson number (Ri) indicated that the airflow was dominated by natural convection. However, the vertical temperature stratification may create discomfort for passengers. Highlights: A method to control thermo-fluid boundary conditions in an airliner cabin mockup. High resolution-data of air and contaminant distribution were provided. Characteristics of air distribution under displacement ventilation.